Rheumatology training in India compared to the United Kingdom - Parthajit Das; Arumugan Moorthy; Balebail Dharmanand (Indian Journal of Rheumatology)
Background: Rheumatology is an emerging specialty in India, and there is a huge demand for trained rheumatologist to satiate the overwhelming musculoskeletal disease burden in India. Rheumatology training in the UK is structured and comprehensive. This study was aimed to explore the strengths and weaknesses in the rheumatology training in India as compared to the UK. Methods: This was an observational semiqualitative study. An online questionnaire was circulated electronically to rheumatology trainees across the UK and India. The questionnaire was designed to explore the curriculum content, training and research opportunities, training assessment methodologies, and employability in two countries. Results: A total of 77 respondents participated in this study, 52% (40/77) were from the UK and 48% (37/77) from India. We noted heterogeneity in the structure and delivery of training with multiple incongruous training curricula being prevalent in India. Institutional academic training supervision was comparable in both countries. UK trainees received comparatively more structured supervision for procedural skills. Indian trainees were proficient with laboratory-based rheumatological and immunological tests. Professional research and academic programs were incorporated in UK training. Mandatory training for generic skills was lacking in India. Specialty exit examination was mandatory in both countries. Employment opportunities were better perceived in the Indian subcontinent. Conclusions: In this study comparing rheumatology training between the UK and India,a lack of structured and coherent national curriculum in India was noted. Harmonisation of rheumatology training in India is essential to be at par with the well-established postgraduate rheumatology training curriculum in developed countries.